Strategic behaviour of polluters during the transition from standard-setting to permits trading - Benoît Laplante; Eftichios Sophocles Sartzetakis; Anastasios P. Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 1997)
Grandfathering of emission permits creates a rent to incumbent firms since a valuable asset is freely distributed to them. In this paper, we examine the strategic behaviour of polluters that anticipate a change in environmental regulation from a standard-setting to tradable emission permits with grandfathering. We focus on the impact of firms' rent-reeking activities on social welfare. We show that anticipation of the change in environmental regulation has two effects: a distributional effect which reduces, or completely eliminates, the distributional bias towards incumbent firms inherent to the grandfathering system and an efficiency effect resulting from the increase in aggregate output and emissions during the base period. Social welfare may increase as a result of the strategic manipulation of emissions.
Keywords: 330; Umweltstandard; Emissionshandel; Spieltheorie; Theorie